Exploring neurofilament light chain as a biomarker for kidney disease: insights, implications, and future directions - Nicholas Aderinto; Gbolahan Olatunji; Emmanuel Kokori; Chinonyelum Emmanuel Agbo; Ikponmwosa Jude Ogieuhi; Ibukunoluwa Victoria Ishola; Victor Oluwatomiwa Ajekiigbe; Oluwaseun Oyewo; Badrudeen Olalekan Alabi; Jonathan Oluwafemi Adeola; David Opeyemi Olaewe; Adetola Emmanuel Babalola (The Egyptian Journal of Internal Medicine)
Abstract Background Neurofilament light chain (NfL) has emerged as a sensitive biomarker for neuronal injury across various neurological disorders. Recent studies suggest that its elevated serum levels are also associated with kidney disease, including chronic kidney disease, acute kidney injury, and diabetic nephropathy. Main body This paper explores the potential of NfL as a diagnostic and prognostic tool in renal medicine, evaluates its clinical implications, and outlines future research directions. We reviewed recent literature on NfL dynamics, the neuro-renal axis, and the role of the neurofilament light chain in kidney disease across PubMed, Embase, Web of Science, Google Scholar, Cochrane Library, and Scopus. We then analyzed the current evidence on the diagnostic and prognostic value of serum NfL levels in various renal conditions and discussed potential therapeutic implications. Elevated serum NfL levels are associated with several kidney diseases, including chronic kidney disease, acute kidney disease, and diabetic nephropathy. Its increased serum level is related to impaired renal clearance, hormonal changes, and inflammatory processes. NfL levels correlate with traditional renal biomarkers, such as serum creatinine and estimated glomerular filtration rate, and offer additional insights into disease progression and patient prognosis. Conclusion NfL holds promise as a novel biomarker for kidney disease, offering potential advantages for early detection, risk stratification, and monitoring disease progression. Future studies should focus on longitudinal and mechanistic studies to elucidate the pathways linking NfL and kidney function, and clinical trials should be conducted to evaluate the effectiveness of NfL-targeted interventions.